Detection and control of power loss due to soiling and faults in photovoltaic solar farms via wireless sensor network - Abid, Ahmed; Obed, Adel; Al-Naima, Fawzi (International Journal of Engineering and Technology, 2018)
Solar photovoltaic (PV) farm output power is highly related to the panel conditions. Soiling causes faults in the PV panels leading to a dras-tic reduction in the system efficiency. In vast solar PV farms, the detection of faults in an individual PV panel is a difficult task since it is usually done manually. In this research, a new design is proposed to detect the production of individual PV panel automatically and periodically to evaluate the condition of each panel in the farm no matter how it is connected in the array. The proposed design allows the user to measure the open circuit voltage (VOC), the short circuit current (ISC) and the delivered power for each PV panel in the farm. It is also capable of controlling each panel to work at the maximum power point using a built in Maximum Power Point Tracking (MPPT) sub-circuit on each solar panel. The presented system depicts a complete wireless sensor network, which does not need any extra wiring and is character-ized by being of low cost, reliable and efficient.